Avalokiteshwara, a renowned Buddhist devotional figure - Wiki commons (2022)
Attribution: Liao_Dynasty_-_Guan_Yin_statue.jpg: Rebecca Arnett from Castleton, Vermont, USAderivative work: Tengu800, CC BY-SA 2.0 <https://creativecommons.org/licenses/by-sa/2.0>, via Wikimedia Commons